Neopterin and Soluble Urokinase Type Plasminogen Activator Receptor as Biomarkers in Dogs with Systemic Inflammatory Response Syndrome - BASBUG, O.; AYDOGDU, U.; AGAOGLU, Z. T, (Journal of the Hellenic Veterinary Medical Society, 2020)
The systemic inflammatory response syndrome (SIRS) is a common cause of mortality in dogs. This study aims to investigate the diagnostic value of markers C-reactive protein (CRP), soluble urokinase-type plasminogen activator receptor (suPAR) and neopterin in dogs with SIRS. The materials of the study consist of 30 dogs with SIRS and 15 healthy dogs that show no clinical symptom, 45 dogs in total. CRP, suPAR and neopterin levels of the serum samples were determined by ELISA using commercial kits. In the study, it was found that CRP, suPAR and neopterin levels of dogs with SIRS were significantly higher (P < 0.001, P < 0.01 and P < 0.01, respectively) than those in the healthy group. The cut-off values for the healthy dogs and dogs with SIRS for CRP, suPAR and neopterin were determined to be 11.20 mg/L, 223.68 ng/L and 3.23 nmol/mL, respectively. At these cut-off values, sensitivity levels were determined as high (92.90%) for CRP, moderate (63.30%) for neopterin, and low (53.30%) for suPAR, and high specificities (93.30%) were determined for all. In conclusion, it was determined that CRP showed the best performance for the detection of systemic inflammatory response in dogs and neopterin and suPAR could be used as an alternative to CRP. It was also argued that further studies were necessary in order to determine diagnosis and prognosis of diseases.